Review of the Learning Alliance for Adaptation in Smallholder Agriculture - Ekong, Julia (2018)
The Learning Alliance for Adaptation in Smallholder Agriculture is a knowledge platform which leverages the strengths, opportunities and diverse audiences of the International Fund for Agriculture (IFAD) and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). The objective of the Learning Alliance is to produce and disseminate evidence for informed policy and implementation of climate-smart agriculture (CSA) interventions by capturing, analyzing and communicating lessons emerging from the IFAD supported global Adaptation in Smallholder Agriculture Programme (ASAP). The Learning Alliance strives to enable agricultural development policy-makers and practitioners make science-based decisions in the context of climate change. The underlying assumption of the Learning Alliance is that the “provision of demand-driven research outputs to policy-makers and practitioners is a key mechanism for improving the effectiveness of adaptation actions among ultimate beneficiaries, in this case smallholder farmers”.